Pengaruh Good Corporate Governance, Rasio Likuiditas Dan Hasil Investasi Terhadap Profitabilitas Pada Asuransi Syariah - Zubaidah Nasution; Wildia Septy Nushaivi (Jurnal Ekonomi Syariah Pelita Bangsa, 2024)
The rapid development of the non-bank financial industry and the increase in Islamic insurance assets and investments can affect financial performance and risk, but it does not rule out the possibility that there are still irregularities in corporate governance. This study aims to analyze the effect of Good Corporate Governance, Liquidity Ratio and Investment Return on Profitability in Islamic Insurance. This study uses quantitative methods using secondary data. The sampling technique used purposive sampling method. Samples that meet the criteria are 15 Sharia Life Insurance companies in 2017-2022. The model used as an analytical tool is multiple linear regression using SPSS 26. The results of this study indicate that partially the Board of Commissioners and Liquidity Ratio have a positive and insignificant effect. Investment returns partially have a positive and significant effect on Profitability (ROA) in Islamic Life Insurance, while simultaneously the variables of the Board of Commissioners, Liquidity Ratio and Investment Results have a significant effect on Profitability in Islamic Life Insurance.